Impact of post-transplant cyclophosphamide with bendamustine on immune reconstitution in young patients undergoing T-cell replete haploidentical bone marrow transplantation: results from a phase Ia/Ib clinical trial - Forrest L. Baker; Forrest L. Baker; Forrest L. Baker; Jessica Stokes; Megan J. Cracchiolo; Dan Davini; Richard J. Simpson; Richard J. Simpson; Richard J. Simpson; Richard J. Simpson; Emmanuel Katsanis; Emmanuel Katsanis; et al. (Frontiers in Immunology, 2025)
IntroductionPost-transplant cyclophosphamide (PT-CY) has been pivotal in controlling graft-versus-host disease (GvHD) following T-cell-replete haploidentical bone marrow transplantation (haplo-BMT). However, the widely adopted regimen is associated with high relapse rates, particularly in patients without GvHD. Our preclinical studies indicate that pre- or post-transplant bendamustine (PT-BEN) may reduce GvHD, enhance graft-versus-leukemia (GvL) effects, and induce significant alterations in the proportion, phenotype, and function of various immune cell subsets.MethodsWe initiated a Phase Ia/Ib, single-center trial with a standard 3 + 3 dose-escalation design, sequentially replacing post-transplant (PT)-CY with BEN (PT-CY/BEN). Multi-parameter flow cytometry and TCR β sequencing of genomic DNA was performed on isolated PBMCs on PT days +30, +60, +100, +180, and +365.ResultsOverall, the PT-CY/BEN (n=14) regimen was associated with earlier neutrophil and platelet engraftment, reduced transfusion requirements, and comparable clinical outcomes to PT-CY (n=10), including survival and relapse rates. PT-CY/BEN patients exhibited distinct immune reconstitution patterns, characterized by earlier CD4+ T-cell recovery, impaired CD8+ T-cell engraftment, and reduced NK-cell counts. Notably there were no significant changes in B-cells, Tregs, or MDSCs. Enhanced T-cell repertoire diversity in the PT-CY/BEN cohort was associated with improved CMV control.ConclusionOur Phase Ia findings demonstrate the well-tolerability of PT-CY/BEN and its association with early engraftment, a more diverse T-cell repertoire, and earlier CD4+ T-cell reconstitution. Future studies are warranted to confirm our findings and investigate potential additional benefits of PT-CY/BEN over PT-CY alone.